MesoTRAP: a feasibility study that includes a pilot clinical trial comparing video-assisted thoracoscopic partial pleurectomy decortication with indwelling pleural catheter in patients with trapped lung due to malignant pleural mesothelioma designed to address recruitment and randomisation uncertainties and sample size requirements for a phase III trial. Issue 1 (5th January 2019) - Matthews, Claire; Freeman, Carol; Sharples, Linda D; Fox-Rushby, Julia; Tod, Angela; Maskell, Nicholas A; Edwards, John G; Coonar, Aman S; Sivasothy, Pasupathy; Hughes, Victoria; Rahman, Najib M; Waller, David A; et al.
Abstract : Introduction: One of the most debilitating symptoms of malignant pleural mesothelioma (MPM) is dyspnoea caused by pleural effusion. MPM can be complicated by the presence of tumour on the visceral pleura preventing the lung from re-expanding, known as trapped lung (TL). There is currently no consensus on the best way to manage TL. One approach is insertion of an indwelling pleural catheter (IPC) under local anaesthesia. Another is video-assisted thoracoscopic partial pleurectomy/decortication (VAT-PD). Performed under general anaesthesia, VAT-PD permits surgical removal of the rind of tumour from the visceral pleura thereby allowing the lung to fully re-expand. Methods and analysis: MesoTRAP is a feasibility study that includes a pilot multicentre, randomised controlled clinical trial comparing VAT-PD with IPC in patients with TL and pleural effusion due to MPM. The primary objective is to measure the SD of visual analogue scale scores for dyspnoea following randomisation and examine the patterns of change over time in each treatment group. Secondary objectives include documenting survival and adverse events, estimating the incidence and prevalence of TL in patients with MPM, examining completion of alternative forms of data capture for economic evaluation and determining the ability to randomise 38 patients in 18 months. Ethics and dissemination: This study was approved by the East of England-Cambridge Central Research Ethics Committee and the Health Research Authority (reference number 16/EE/0370). We aim to publish the outputs of this work in international peer-reviewed journals compliant with an Open Access policy. Trial registration: NCT03412357 .